2018
DOI: 10.1002/cplu.201800515
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Hierarchically Porous Lead/Carbon Composite and Its Application in Lead‐Carbon Batteries

Abstract: A novel and scalable lead-modified phenolic resin-based carbon material (Pb/PRC) has been successfully prepared by using leadmodified phenolic resin (Pb/PR) as a precursor, toluene as a pore-forming agent, and KOH as an activating agent. The Pb/ PRC composite presents a hierarchically porous nanosphere structure, and this structure contributes to prolong its cycling life under high-rate partial state-of-charge (HRPSoC) operation. Pb/PRC with nano-lead can effectively inhibit hydrogen evolution and provide pseu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…B L W A et al [6] proposed and prepared a new type of nano-lead-doped mesoporous carbon composite material as a negative electrode additive, and experimental results showed that through NaOH activation and air oxidation, porous carbon can obtain more mesoporous volume and appropriate acidic groups, enabling the mesoporous system to load more nano-lead deposits, and limit the size of the deposits to the nanometer level through its local effects, thereby ensuring more significant inhibition of hydrogen evolution and better Pb/PbSO4 reversibility; Li J et al [7] synthesized a lead-carbon composite NSCG@PbO with nano-lead oxide and multifunctional porous carbon nucleated on the graphene framework by sol-gel pyrolysis, and applied it to the negative electrode of lead-carbon batteries, the unique three-dimensional porous lead-carbon network structure of NSCG@PbO limits the formation of large PbSO4 particles, effectively increases the porosity of lead-carbon electrodes, maintains the electrochemically active surface area of lead-carbon batteries, and PbO functional groups and COO functional groups embedded in the graphene framework further enhance the interfacial performance of electrode and electrolyte, inhibited the hydrogen evolution during the long cycle, and successfully enhanced the reversibility of the deep discharge of the battery; Zhang Y S et al [8] synthesized three-dimensionally constructed graphene/nano-lead (SCG-Pb) composites by electrodeposition, the study showed that SCG-Pb has good electrical conductivity, rich pore structure and excellent dispersion, an efficient conductive network can be constructed in the negative electrode active material, which is beneficial to the ion exchange between the negative electrode active material and the electrolyte, accelerates the dynamic process of the negative electrode, and effectively suppresses the irreversible sulfation of the negative electrode, thereby improving the capacity and cycle life of the battery; Xie JM et al [9] prepared lead oxide and carbon composites (LC) by pyrolysis of highly graphitized porous carbon and PbCO3 mixtures, the test results show that the density difference between Pb and C can be eliminated by using LC materials, thus, they are uniformly mixed, effectively limiting the accumulation of irreversible PbSO4, and the presence of -Pb-COO chemical bonds can enhance the stability of the lead-carbon electrode. Compared with the control battery, when the LC material is added to the negative electrode active material, the initial specific discharge capacity increased by 16.5%; Gao Y [10] prepared a new lead-modified phenolic resin-based carbon material (Pb/PRC) with lead-modified phenolic resin (Pb/PR) as precursor, toluene as pore-forming agent, and KOH as activator, he hierarchical porous nanosphere structure exhibited by it helps to prolong its cycle life under HRPSoC, effectively suppress hydrogen evolution and improve specific capacitance; Yi T H et al [11] synthesized hierarchically porous carbon with in-situ grown carbon nanotube clusters (HPC-CNTs) by transition metal catalytic cracking, and used as an additive to suppress the irreversible sulfation of the negative electrode. This synthetic method not only established a stable connection point between HPC and carbon nanotubes, but also avoided the aggregation of carbon nanotubes.…”
Section: Changing the Binding Methods Of Lead-carbon Materialsmentioning
confidence: 99%
“…B L W A et al [6] proposed and prepared a new type of nano-lead-doped mesoporous carbon composite material as a negative electrode additive, and experimental results showed that through NaOH activation and air oxidation, porous carbon can obtain more mesoporous volume and appropriate acidic groups, enabling the mesoporous system to load more nano-lead deposits, and limit the size of the deposits to the nanometer level through its local effects, thereby ensuring more significant inhibition of hydrogen evolution and better Pb/PbSO4 reversibility; Li J et al [7] synthesized a lead-carbon composite NSCG@PbO with nano-lead oxide and multifunctional porous carbon nucleated on the graphene framework by sol-gel pyrolysis, and applied it to the negative electrode of lead-carbon batteries, the unique three-dimensional porous lead-carbon network structure of NSCG@PbO limits the formation of large PbSO4 particles, effectively increases the porosity of lead-carbon electrodes, maintains the electrochemically active surface area of lead-carbon batteries, and PbO functional groups and COO functional groups embedded in the graphene framework further enhance the interfacial performance of electrode and electrolyte, inhibited the hydrogen evolution during the long cycle, and successfully enhanced the reversibility of the deep discharge of the battery; Zhang Y S et al [8] synthesized three-dimensionally constructed graphene/nano-lead (SCG-Pb) composites by electrodeposition, the study showed that SCG-Pb has good electrical conductivity, rich pore structure and excellent dispersion, an efficient conductive network can be constructed in the negative electrode active material, which is beneficial to the ion exchange between the negative electrode active material and the electrolyte, accelerates the dynamic process of the negative electrode, and effectively suppresses the irreversible sulfation of the negative electrode, thereby improving the capacity and cycle life of the battery; Xie JM et al [9] prepared lead oxide and carbon composites (LC) by pyrolysis of highly graphitized porous carbon and PbCO3 mixtures, the test results show that the density difference between Pb and C can be eliminated by using LC materials, thus, they are uniformly mixed, effectively limiting the accumulation of irreversible PbSO4, and the presence of -Pb-COO chemical bonds can enhance the stability of the lead-carbon electrode. Compared with the control battery, when the LC material is added to the negative electrode active material, the initial specific discharge capacity increased by 16.5%; Gao Y [10] prepared a new lead-modified phenolic resin-based carbon material (Pb/PRC) with lead-modified phenolic resin (Pb/PR) as precursor, toluene as pore-forming agent, and KOH as activator, he hierarchical porous nanosphere structure exhibited by it helps to prolong its cycle life under HRPSoC, effectively suppress hydrogen evolution and improve specific capacitance; Yi T H et al [11] synthesized hierarchically porous carbon with in-situ grown carbon nanotube clusters (HPC-CNTs) by transition metal catalytic cracking, and used as an additive to suppress the irreversible sulfation of the negative electrode. This synthetic method not only established a stable connection point between HPC and carbon nanotubes, but also avoided the aggregation of carbon nanotubes.…”
Section: Changing the Binding Methods Of Lead-carbon Materialsmentioning
confidence: 99%